If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(7 + -1x) + 2whenx = -4 (7 * x + -1x * x) + 2whenx = -4 (7x + -1x2) + 2whenx = -4 Reorder the terms: 2ehnwx + 7x + -1x2 = -4 Solving 2ehnwx + 7x + -1x2 = -4 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-7x' to each side of the equation. 2ehnwx + 7x + -7x + -1x2 = -4 + -7x Combine like terms: 7x + -7x = 0 2ehnwx + 0 + -1x2 = -4 + -7x 2ehnwx + -1x2 = -4 + -7x Add 'x2' to each side of the equation. 2ehnwx + -1x2 + x2 = -4 + -7x + x2 Combine like terms: -1x2 + x2 = 0 2ehnwx + 0 = -4 + -7x + x2 2ehnwx = -4 + -7x + x2 Divide each side by '2hnwx'. e = -2h-1n-1w-1x-1 + -3.5h-1n-1w-1 + 0.5h-1n-1w-1x Simplifying e = -2h-1n-1w-1x-1 + -3.5h-1n-1w-1 + 0.5h-1n-1w-1x Reorder the terms: e = -3.5h-1n-1w-1 + -2h-1n-1w-1x-1 + 0.5h-1n-1w-1x
| 20=t-70 | | 4(x+8)-7whenx=8 | | lg(x+3)+lg(1-x)=lg(4x+8) | | v-4.7=23.8 | | 59+19f=8f+5 | | k-16=7 | | 15=c-40 | | 2+n=95 | | -54=c-38 | | a-33=66 | | 19r+39=9+4r | | -16-7x=208-42x | | 8000(d)=-5d^2+450d-1000 | | 7x-7=(-x)+1 | | 45b-83=25-9b | | 9a^2+a-30=0 | | 33x^2+x+8=12 | | x^2+6x+3=-2 | | 2=48 | | 2=48r | | 12x+23=68+7x | | y=4-7(8/13)/2 | | c^4-1296=0 | | X/12-1/2x=1/6 | | 90=6(6r+3) | | -5(7n-5)=220 | | 4x+5=8x+14 | | x^2-3x-10=30 | | 56x^2-16x=0 | | 2n=3+3/n | | 8a+3(2-a)=82 | | 99=7(k+5)+8 |